Exploring the knowledge, thoughts, and experiences of virtual reality training in elite football and baseball - Dowsett, R.; Kinrade, N.; Lawson, D.; Whiteside, D.; Barnett, C.; Magistro, D.; Wilkins, L. (Research Square, 2022)
Despite the perceived benefits of implementing virtual reality (VR) training in elite sport (Gray, 2019), arguably the most important element - the thoughts, knowledge, and experiences of practitioners - has been largely understudied. Therefore, the present study aimed to explore practitioners` knowledge of VR, current and past usage, important factors for implementation, and perceived obstacles in elite football and baseball via an online questionnaire. Football respondents (n = 25) represented practitioners from major football leagues across the world, and baseball respondents (n = 15) represented practitioners from Major League Baseball. Both football and baseball respondents reported that the most important factor for implementation of VR training was improvement in on-field performance, whether this be mental, tactical, or technical. Furthermore, both football and baseball respondents highlighted cost as the biggest obstacle at their current club. Notably, Mann-Whitney U tests revealed that football respondents perceived coach (p = .02) and executive approval (p < .001) as significantly greater obstacles than baseball respondents. Regression analyses showed that a lack of executive approval was best predicted by the obstacle of cost (p = .02), whereas a lack of coach approval was best predicted by general negative perceptions of VR (p < .01). Mann Whitney U tests also revealed that football respondents had a significantly higher mean rating for obstacles (p < .01) and significantly lower perceived knowledge of sport-specific VR than the baseball respondents (p < .001). These findings have considerable implications with regard to the potential application of VR training in football and baseball.